Tiered expatriation: A social relations approach to staffing multinationals. Issue 5 (3rd September 2018) - Zheng, Yu; Smith, Chris
Abstract : This article applies a social relations discourse to examine the use of expatriates in Chinese multinational companies (MNCs). Expatriates are analyzed based on two sets of social relations: the social functions of expatriates (which include the global function of capital and the collective function of labor) and the pathways of expatriation (which include intra‐ and interfirm transfers). In particular, the framework incorporates the collective function of labor into the analysis of expatriation, which has received limited attention in the existing international HRM literature. Conceptually, the social relations discourse allowed us to frame staffing in an open system in which HR practices involving expatriation are shaped by the intersections between the choices of MNCs, the actions of workers, and the mediation of institutional players. Empirically, this article presents three case studies of Chinese MNCs in Europe to illustrate the tiered expatriation of managerial staff, technicians, and operational workers from interchangeable sources of labor. The HR policy implications suggest greater diversity in the formation of international staffing for MNCs.